CASE STUDY OF THE EFFECT OF CARBOHYDRATE METABOLISM IN COMBINATION OF NPK FERTILIZER AND UREA FERTILIZER ON THE GROWTH OF CORN (ZEA MAYS) PLANTS IN CIREBON REGENCY - Chiska Nova Harsela (Green Publisher, 2022)
The purpose of this study was to determine the best composition of the use of NPK fertilizer and urea fertilizer in the growth and yield of maize in Cirebon Regency. The research was conducted on a rainfed agro-ecosystem owned by farmers in Cirebon Regency, from January to March 2022. The production technology was carried out by Perfect Soil Processing (PSP) with a spacing of 75 cm x 40cm, 2 plants/hole. The study was arranged using a Randomized Block Design (RBD) with 3 replications and 10 combinations of fertilizer doses as treatment. Fertilization was carried out 2 (two) times at the age of 10 days after planting with a dose of 30% Urea and 30% NPK, as well as all SP-36 and KCl, then at 35 DAP with a dose of 70% Urea and 70% NPK. To see the effectiveness of alternative NPK fertilizers, several treatments were combined and some were not with a single fertilizer (Urea). Fertilization is done by tugal about 5 cm next to the plant hole. The conclusion obtained from the results of the field study is that the application of a combination of alternative NPK fertilizers with Urea has better effectiveness than the single application of NPK. However, it had no significant effect on the components of plant height growth.